Ontological metaphor in the language of the series The Leatherstocking tales by James Fenimore Cooper - Mai, The Manh (Technium Social Sciences Journal, 2025)
In most cultures, the convention of human experiences into material forms allows us to perceive events, activities, emotions, and ideas as objects or materials, which are forms of ontological metaphor. Considering experiences as an entity allows us to talk about it, quantify it, and identify its particular aspects. Depending on different purposes, ontological metaphors are used to promote expressive capabilities in each specific case. This article studies the analysis of ontological metaphors in The Leatherstocking Tales by James Fenimore Cooper based on the metaphor theory of Lakoff and Johnson. The author uses qualitative methods to conduct research focusing on written data from selected works of Cooper. Events and actions are conceptualized as objects, activities are conceptualized as materials, and states are conceptualized as containers so that an event exists in space and time and has defined boundaries. The purpose of this study is to help students understand the impact of ontological metaphors in novels. This will help them increase their awareness of language acquisition and the use of metaphors in American culture.